The Influence of Crown Ferrule on Fracture Resistance of Endodontically Treated Maxillary Central Incisors - Jovanovski Sasho; Popovski Julie; Dakskobler Alesh; Marion Ljubo; Jevnikar Peter (Balkan Stomatological Society, 2017)
Background: Prefabricated zirconia posts can contribute to increasing the fracture resistance of the endodontically treated teeth. Purpose. This in vitro study compared the fracture resistance of endodontically treated central maxillary incisors prepared with 2 mm ferrule length to the ones without ferrule.